DAMPAK IMPLEMENTASI TEKNOLOGI DIGITAL DALAM ADMINISTRASI PERPAJAKAN TERHADAP PENINGKATAN KEPATUHAN WAJIB PAJAK DI KOTA MAKASSAR - Mawar; Ihsan Burhanuddin, Chairul; Hasanuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Taxpayer compliance is key to the success of the taxation system, yet complicated administrative processes often hinder its improvement, including in the payment of Motor Vehicle Tax (PKB) in Makassar City. Digital technology is expected to be a solution that makes it easier for taxpayers to fulfill their obligations. This study aims to determine the impact of digital technology implementation in tax administration on increasing taxpayer compliance in Makassar City. This study uses a quantitative method with a survey approach. Primary data were obtained through questionnaires distributed to 100 respondents selected using a purposive sampling technique. The data were analyzed using simple linear regression with the help of SPSS, including validity tests, reliability tests, partial tests (t-test), and coefficient of determination tests. The results show that the implementation of digital technology has a positive and significant effect on increasing taxpayer compliance. These findings have implications for local governments in designing more effective tax service digitalization policies to encourage sustainable taxpayer compliance.